A framework of modelling slip-controlled crack growth in polycrystals using crystal plasticity and XFEM. Issue 4 (April 2021) - Zhang, P.; Lu, S.; Baxevanakis, K.P.; Zhao, L.G.; Yu, T.Y.; Zhou, R.X.
Abstract: Short cracks tend to develop at high and irregular rates compared to macroscopic cracks, making the prediction of fatigue life a challenging task. In this work, a numerical framework combining crystal plasticity model and the Extended Finite Element Method (XFEM) is applied to study the slip-controlled short crack growth in a polycrystal superalloy RR1000. The model is calibrated from experiments and used to evaluate short crack growth paths and rates. Two fracture criteria are used and compared: the onset of fracture is controlled by the total and individual cumulative shear strain respectively, and the crack grows either perpendicular to the direction of maximum principal strain or along crystallographic directions.